Acurácia diagnóstica de um painel de sinais e sintomas clínicos para a detecção da deficiência de ferro em doadoras de sangue - Joseph, Jamesly (2019)
ABSTRACT Iron deficiency (ID) is a health condition in which the availability of iron is insufficient to meet the needs of the body. This condition remains the most common cause of anemia, accounting for half of all cases of anemia worldwide, prevailing even in developed countries. Clinically, it manifests itself through generalized fatigue, pica, hair loss, dysphagia, brittle nails, among others. Recent data show that the frequency of ID is high in blood donors, and that this situation is even more complex in women at reproductive ages due to losses related to menstruation, pregnancy and lactation. However, a high proportion of blood donors are deficient in iron despite sufficient hemoglobin levels for donation. In this study, we evaluated the accuracy of two clinical instruments (CI), based respectively on anamnesis and physical examination (PE), with the objective of detecting iron deficiency without anemia among female blood donors who attended blood collection unit of a public blood center in Brazil (HEMOAM),thus providing data for an improvement in standard screening quality for donation. The study was cross-sectional, descriptive and analytical. The study population consisted of 221 approved blood donors in the blood donation screening process at the HEMOAM central collection unit. The clinical data were obtained by means of an instrument for anamnesis and PE. The anamnesis CI tool consisted of three questions, focused on: (1) pica symptoms; (2) hair loss; and (3) nail changes, and the CI of PE consisted of a standardized physical examination, we evaluated (1) pallor of the palpebral conjunctiva, and (2) nail weakness. Determinations of serum ferritin, transferrin saturation, serum iron and hemogram were performed. The accuracy of the CI was measured by sensitivity, specificity, predictive values, and likelihood ratios. The mean age of the population was 31 years. The frequency of blood donors with ID was 40% (ferritin <30 ng/ ml), and 9.9% of the donors had a more severe deficiency (ferritin <30 ng/ml).Regarding the risk factors for ID, significant, yet a mild correlation (p<0.05) was observed between ferritin and duration of menstruation (P=0.0037).Regarding the use of the CI, none of the analyzes of the clinical criteria used for the diagnosis of ID presented individually acceptable values of accuracy. By analyzing the three questions in the clinical history together and using the affirmative criterion for only one of them, we noticed a clinically significant increase in the sensitivity of this criterion in the different cutoff points of ferritin and hemoglobin (Hb),as well as higher values of predictive value negative (77%, 94% respectively with ferritin <12ng/ml).The rationale for this strategy was to try to create a panel of questions that applied to the screening, xi could be used to exclude donors with higher risk of ID, although some of these results were false positives. Finally, when considered together all the variables that indicate ID, from the clinical point of view presented higher values of sensitivity and negative predictive value, indicating the possibility of using this clinical criterion as a tool for clinical screening for ID among females blood donors, particularly in areas with higher ID prevalence. Keywords: Iron deficiency. Blood donation. Signs and symptoms.